A History of Oil Palm Production in Nigeria, 1945 - 1970 - Oladiti Abiodun Akeem; Faruq Oluwatobiloba Abdulsalam; Ajibola Temitopebolaji; Oyewale Peter Oluwaseun (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2024)
Oil palm production is an important economic activity in agriculture for the production of cooking oil and raw materials for soap, body cream and befoul. Oil palm production in the 1950’s significantly helped to boost the Nigerian economy than any other natural resources found in the region.Oil palm production had a huge impact on the development agricultural production of palm oil for cooking and raw materials for cottage industries in Nigeria. The production of oil palm served to boost local trade and economy of the people before the discovery of crude oil that consequently led to the oil boom era in the 1970s. This seriously affected oil palm production and its expansion and development for exports to earn foreign exchange. The outbreak of the World War II and the civil war in Nigeria also hindered the production of Oil Palm. This had implication on the net foreign exchange earned from agriculture in Nigeria in the 1970s. Oil palm production reached its peak during this period and declined after the neglect in the investment on agriculture.